2003
DOI: 10.1108/02621710310454860
|View full text |Cite
|
Sign up to set email alerts
|

Management development in Ireland: the new organizational wealth?

Abstract: Drawing upon survey data, we assess the current state of management development in Ireland and we identify policy, practice and structural contingencies that help to explain variations in the volume of management development activity undertaken at organizational level. The data show that the level of management development, as measured by the number of days per annum, has increased in recent years with 70 percent of managers in our sample now receiving between one and five days training per year. The mean numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 69 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…While there is no consensus in the literature about what may constitute 'best practice' MD practices, there is some common agreement that the following practices should be present to ensure that MD is effective: diagnosis and design of training, career development opportunities and the subsequent evaluation of MD activity (see, Employment Relations Research Unit 1999; Heraty and Morley 2003;D'Netto et al 2008;McDonnell 2008). In order to factor in the potential effects of the global economic crisis, MD expenditure post-2007 is also included in the analysis.…”
Section: Policies and Systemsmentioning
confidence: 99%
“…While there is no consensus in the literature about what may constitute 'best practice' MD practices, there is some common agreement that the following practices should be present to ensure that MD is effective: diagnosis and design of training, career development opportunities and the subsequent evaluation of MD activity (see, Employment Relations Research Unit 1999; Heraty and Morley 2003;D'Netto et al 2008;McDonnell 2008). In order to factor in the potential effects of the global economic crisis, MD expenditure post-2007 is also included in the analysis.…”
Section: Policies and Systemsmentioning
confidence: 99%
“…Moreover, the existing evidence is regarded as inconclusive and contradictory (Heraty and Morley, 2003;Morgan et al, 2003;Storey, 2004). Jayawarna et al (2007) found that formal training was more signifi cantly associated with enhanced business performance than informal training.…”
Section: Introductionmentioning
confidence: 96%
“…This is used as a measure to indicate the extent to which the firm's human resources are regarded as an investment central to organisational success. Reliable data on this type of expenditure are not easy to come by in some companies due in no small part to the complex structures of organisations (Heraty and Morley, 2003;Edwards et al, 2007). This proved to be the case in a number of organisations with some respondents unable to even provide a range of training and development expenditure.…”
Section: Training and Development Expenditurementioning
confidence: 99%